The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s40693-017-0069-y
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variations in macroinvertebrate communities from the tributaries in the Three Gorges Reservoir Catchment, China

Abstract: Background: The seasonal variations in macroinvertebrate communities in tropical, temperate and subarctic regions have been observed and well documented to date, but similar studies conducted in subtropical rivers at the regional scale are relatively rare. In this paper, the macroinvertebrate communities from the main tributaries in the Three Gorges Reservoir Catchment (TGRC) were investigated as a function of the four seasons to explore the temporal variations in macroinvertebrate communities and further test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 59 publications
0
6
0
1
Order By: Relevance
“…The high representativeness of studies applying invertebrate indices could be related to the wide distribution of these taxa and their important role as bioindicators in freshwater ecosystems. Worldwide studies have demonstrated that anthropogenic activities exert a significant effect on the diversity of sensitive invertebrates (Mehari et al 2014;Chi et al 2017) Domínguez and Fernández 1998), are not only ecologically meaningful, but they could also be integrated into citizen science approaches (Penrose and Call 1995;Nerbonne and Vondracek 2003;Edwards 2016;Rae et al 2019) and thereby enhance dialogue between science and society (Wenger et al 2009). The United Nations has called for increased public participation in scientific research, to benefit professionals, the public, and the planet (Quinlivan et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The high representativeness of studies applying invertebrate indices could be related to the wide distribution of these taxa and their important role as bioindicators in freshwater ecosystems. Worldwide studies have demonstrated that anthropogenic activities exert a significant effect on the diversity of sensitive invertebrates (Mehari et al 2014;Chi et al 2017) Domínguez and Fernández 1998), are not only ecologically meaningful, but they could also be integrated into citizen science approaches (Penrose and Call 1995;Nerbonne and Vondracek 2003;Edwards 2016;Rae et al 2019) and thereby enhance dialogue between science and society (Wenger et al 2009). The United Nations has called for increased public participation in scientific research, to benefit professionals, the public, and the planet (Quinlivan et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Con los grupos analizados de los macroinvertebrados a través de órdenes, familias, o géneros para evaluar la calidad del agua, se calculó el índice biótico IBMWP "Biological Monitoring Working Party" modificado y adaptado para el río Chotano [1], [15], además se calculó el índice de riqueza total de EPT (Ephemeroptera, Plecoptera y Trichoptera).…”
Section: Análisis De Los Datos Halladosunclassified
“…However, some community variations in models were still unexplained. One possibility was that low investigation frequency may let slip some key stages of macroinvertebrates life histories; secondly, other factors related to macroinvertebrate assemblages may also influence the spatio-temporal variances, such as biota interaction, substrate composition [62], macrophyte species composition and abundance [24,63], hydraulic and hydrological parameters [25], and human activities [21,64]. Furthermore, short time scale in situ measurements usually hardly capture the spatio-temporal distribution of emergent phenomena such as insect emergence and hatching [65].…”
Section: Relationship Between Assemblages and Environmental Variablesmentioning
confidence: 99%
“…Spatial and temporal researches on macroinvertebrate communities are the basis of further studies, and have been investigated by many researchers [19][20][21][22]. Although assessment methods based on macroinvertebrate are becoming more and more popular in China, the lack knowledge of the environmental and biological data in many regions hinders the development of bio-assessment [23].…”
Section: Introductionmentioning
confidence: 99%